PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN KRISFITE SPICY DI KABUPATEN TULUNGAGUNG - Mohamad Andi Saputro; Maria Agatha SWH (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2022)
This study aims to determine the effect of price and product quality on consumer satisfaction with spicy krisfite with a study at the spicy krisfite outlet, Kalidawir sub-district, Tulungagung regency. Where this research was conducted with the type of quantitative research and ex post facto method using simple random sampling technique. The price variable is measured by price affordability, price suitability with service quality, price competitiveness, price suitability with benefits. Product quality variables are measured by ease of use, durability, clarity, function of product size diversity. Furthermore, the variable of consumer satisfaction is measured from the fulfillment of consumer expectations, the desire to use the product, recommend to other parties, service quality, location. Researchers used the Simple Random Sampling technique to determine the number of samples used, which was taken 30% of the total population. The sample used in this study were 112 respondents with data retrieval via google form. The results of the study indicate that the price and product quality have a partial effect on consumer satisfaction.